Pengaruh Biaya Produksi, Volume Penjualan Dan Harga Jual Terhadap Laba Bersih Perusahaan Pada CV. Proma Tun Saroyyan Probolinggo - Khusnul Chotima; Joni Hendra; Tatik Amani (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
This study intends to identify the effect individually or partially between production costs (X1), sales volume (X2) and selling price (X3) on the company’s net profit at CV. Proma Tun Saroyyan Probolinggo. The research method using is quantitative. The population used is production cost data, sales data, and profit and loss statements on CV. Proma Tun Saroyyan Probolinggo with a sample of 36 using purposive sampling technique or selected based on predetermined criteria. The data sources used are main data and supporting data. Data is collected using interviews and documentation and managed by data analysis methods such as normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple regression test, coefficient of determination test and hypothesis test. According to research findings, production costs have a significant negative effect on net income, while sales volume and selling price have a significant positive effect on net income at CV. Proma Tun Saroyyan.